Internet marketing in SME - Vorel, Lukáš (2010)
This thesis aims to explore concrete ways of application of internet marketing for promotion of a small service oriented business-to-business (B2B) company in broader context of the so-called new economy. To support the validity of the presented applications the thesis first draws on well-established theory of marketing concepts. In the second part of the paper, the role of internet marketing in business strategy of small and medium sized enterprises is explored. The thesis then continues with detailed description of particular tools of internet marketing and discusses their relevance and most appropriate application in the chosen field. In the application part of this thesis, the tools of Google Search Engine Marketing, which are perceived as the most efficient agent of small business promotion, are field-tested in a real small business promotion campaign. Finally, the thesis concludes with discussion of possibilities of future development in the field of internet marketing and sums up the overall findings of this paper. Throughout this thesis, the examined new technologies are regarded through the lenses of practical experience reported by their users and, at the same time, with consideration to established theoretical framework.